Old Believers Church in Lithuania (1918–1926): The Restoration and Recognition of Parishes, the Legitimation of the Church, and the Problems of Autonomy - Potašenko, Grigorijus (Lietuvos istorijos studijos, 2020)
The purpose of this article is to research in more detail the restoration of the Old Believers parishes and their recognition during the interwar Lithuania (excluding Vilnius region) from 1918 to 1923, as well as to analyse the legalization of the Old Believers’ Church of Lithuania and the problems of practical establishment of religious autonomy in this period. The main focus is on three new problems: the situation of the Old Believers’ parishes in the country at the beginning of 1918, taking into account the mass migration to the depths of Russia from 1914 to 1915; the restoration of Old Believers parishes and the legalization (registration) of their religious activities from 1918 to 1922, during their mass repatriation to Lithuania; and focus on some problems of the practical consolidation of Old Believers’ Church of Lithuania autonomy from 1923 to 1926. The research is based mostly on new archival data, as well as on the analysis and interpretation of Lithuanian and partly foreign historiography on this topic. The study suggests that due to the mass migration of Old Believers to the East between 1914 and 1915, the future Lithuanian territory retained a much thinner congregation network and in turn had fewer parishes members by the beginning of 1918. Therefore, the mass repatriation of the Old Believers from Soviet Russia from the spring of 1918 to 1922 to a large extent explains why the recovery of many of their parishes in Lithuania has been rather slow. After the establishment of the central institutions of the Church in May 1922, the Lithuanian Old Believers’ Church was legalized on the basis of “Provisional regulations concerning the relationship between the organization of Old Believers in Lithuania and the Lithuanian government” on the May 20, 1923. Therefore, for the first time in history in 1923 the Lithuanian Old Believers Church was legally recognized in a certain state and formally received equal rights with other recognized denominations. At that time, Lithuania was the first country in Central and Eastern Europe to officially recognize the Old Believers (Pomorian) Church.
Keywords: Old Believers; Lithuania; recognition of parishes; the Old Believers Church; religious autonomy